Determinants of Pertamina Global Bond Yield - Andrawina Kartika Sari (Budapest International Research and Critics University, 2022)
This paper aims to recognize the determinant factors that influence the yield of PERTAMINA’s bond. The data used was 10 years of time-series from the year 2011 which was the first time PERTAMINA issued bond, until 2021. The result is the crude oil price, foreign exchange, and the yield of US Treasury bill has strong influence the yield of PERTAMINA both simultaneously and partially.